Design and Implementation of Employee Attendance and Payroll Information System Using Desktop-Based Application - Nguyen Thi Huong; Nguyen Van Minh; Tran Thi Lan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Attendance and payroll management remain among the most critical operational functions in any organization, irrespective of size or industry sector. Persistent inefficiencies in these processes — arising from manual data entry, paper-based recording, or the use of disconnected software tools — often translate into direct financial losses, reduced employee morale, and exposure to regulatory non-compliance. This study reports on the design and implementation of a desktop-based Employee Attendance and Payroll Information System (EAPIS) intended to automate these processes for small-to-medium enterprises (SMEs). Development followed the System Development Life Cycle (SDLC) under the Waterfall model, structured into five sequential stages: requirements analysis, system design, implementation, testing, and maintenance. The application was built using Visual Basic .NET (VB.NET) as the programming language, with Microsoft SQL Server 2019 serving as the relational database management system. Core modules cover employee data management, daily attendance recording, automated salary computation, and report generation. System evaluation paired black-box functional testing with User Acceptance Testing (UAT) involving ten respondents. The result: a 100% functional test pass rate and an average UAT satisfaction score of 4.58 out of 5.0 — figures that support the system's reliability, accuracy, and ease of use. These findings suggest that desktop-based information systems remain a workable, cost-efficient option for organizations seeking to modernize human resource operations without the overhead of a full enterprise resource planning (ERP) deployment.